Prevention of Brain Metastases - Bovi, Joseph A. (Frontiers in Neurology, 2018)
Brain metastases are the most common intracranial neoplasm. The incidence of brain metastases is projected to rise because survival rates of lung cancer, breast cancer, and melanoma continue to improve (1). The brain is being identified as a sanctuary site for harboring metastases despite excellent control of extracranial disease. This is thought to occur because the drug therapies that control extracranial disease have limited central nervous system (CNS) penetration. The development of brain metastases is a devastating diagnosis affecting both quality of life (QOL) and survival. Symptoms after diagnosis can include headache, nausea, vomiting, seizure, neurocognitive decline and focal neurologic deficit. Some of these symptoms can be irreversible even after successful treatment of intracranial disease. Treatment of brain metastases often necessitates surgery and radiation. There have been some reports of systemic therapies offering an intracranial response however long-term data is lacking. These treatments for CNS metastases can also lead to neurocognitive sequelae impacting quality of life. Therefore, preventing disease from spreading to the brain is a topic that has generated much interest in oncology. Prophylactic cranial Irradiation (PCI) has been used in leukemia, small cell lung cancer (SCLC), and non-small cell lung cancer (NSCLC). While showing effectiveness in preventing intracranial disease development, its carries with it side effects of neurocognitive decline that can affect QOL. There are clinic trials exploring novel delivery of PCI and concurrent neuroprotective drug therapy to try to mitigate these neurocognitive sequelae. These will be important trials to complete, as PCI has shown promise in controlling disease and prolonging survival in select patient populations. There are also drug therapies that have shown efficacy in preventing CNS metastases development. This review will explore the current therapies available to prevent CNS metastases.